A generalized dynamic stress-strength interference model under δ-failure criterion for self-healing protective structure. (January 2023) - Ye, Kewei; Wang, Han; Ma, Xiaobing
Highlights: A novel generalized SSI model considering time-varying shock magnitude and stochastic degradation strength is proposed. δ -failure criteria under intact state and healing state are combined into the generalized SSI model to analyze the reliability of self-healing protective structure. An effective algorithm based on Gauss-Legendre quadrature formula and hierarchical iteration method is proposed to solve the reliability under different initial states. The discrepancy of reliability between different initial states is discussed which is helpful for the availability analysis of reusable components. Abstract: Traditional dynamic stress-strength interference (SSI) models usually assume that a failure occurs when the magnitude of a shock exceeds the strength. The assumption holds in most circumstances, while it is not applicable for self-healing protective structure which go through a recovery process after each shock. In this paper, a generalized dynamic SSI model combined with the δ -failure criterion is proposed to analyze the reliability for self-healing protective structure. Particularly, the shock is modeled as a non-homogenous Poisson process with stochastic time-varying magnitude, and the strength is modeled as a stochastic degradation path. Two different initial states (i.e., intact state and healing state) are considered under the δ -failure criterion. Then, a Gauss-Legendre-based hierarchical iteration algorithm is established to solve the complex reliability function including multiple internal and external nested integrations. Numerical solutions which can significantly improve the computational efficiency are provided. Finally, a simulation study and a real application to spur gear reducer are provided to illustrate the effectiveness of the proposed model and method.